Annual and seasonal variability of wet day frequency in West Bengal, India - PATIL, S. G.; MAJUMDER, A. (MAUSAM, 2017)
The monthly wet day frequency data of West Bengal for period 1901-2000 were analyzed to know annual and seasonal variability over decades along with annual, pre-monsoon, monsoon, post-monsoon and winter trends. The non-parametric approach (Mann-Kendall) revealed that the most of the districts shows the decreasing trend during monsoon and increasing trend during pre, post monsoon and in winter season. The changes observed in the statistical parameters (mean, SD, coefficient of skewness and kurtosis) during different decades which reflect the changing pattern of wet-day frequency in West Bengal.